Knockin’ on Egg’s Door: Maternal Control of Egg Activation That Influences Cortical Granule Exocytosis in Animal Species - Rojas, Japhet; Hinostroza, Fernando; Vergara, Sebastián; Pinto-Borguero, Ingrid; Aguilera, Felipe; Fuentes, Ricardo; Carvacho, Ingrid (Frontiers in Cell and Developmental Biology, 2021)
Fertilization by multiple sperm leads to lethal chromosomal number abnormalities, failed embryo development, and miscarriage. In some vertebrate and invertebrate eggs, the so-called cortical reaction contributes to their activation and prevents polyspermy during fertilization. This process involves biogenesis, redistribution, and subsequent accumulation of cortical granules (CGs) at the female gamete cortex during oogenesis. CGs are oocyte- and egg-specific secretory vesicles whose content is discharged during fertilization to block polyspermy. Here, we summarize the molecular mechanisms controlling critical aspects of CG biology prior to and after the gametes interaction. This allows to block polyspermy and provide protection to the developing embryo. We also examine how CGs form and are spatially redistributed during oogenesis. During egg activation, CG exocytosis (CGE) and content release are triggered by increases in intracellular calcium and relies on the function of maternally-loaded proteins. We also discuss how mutations in these factors impact CG dynamics, providing unprecedented models to investigate the genetic program executing fertilization. We further explore the phylogenetic distribution of maternal proteins and signaling pathways contributing to CGE and egg activation. We conclude that many important biological questions and genotype–phenotype relationships during fertilization remain unresolved, and therefore, novel molecular players of CG biology need to be discovered. Future functional and image-based studies are expected to elucidate the identity of genetic candidates and components of the molecular machinery involved in the egg activation. This, will open new therapeutic avenues for treating infertility in humans.